Transgenerational transmission of psychopathology: when are adaptive emotion regulation strategies protective in children? - Łuczejko, Arleta; Werkmann, Naomi Leona; Hagelweide, K.; Stark, R.; Weigelt, S.; Christiansen, H.; Kieser, Meinhard; Otto, K.; Reck, C.; Steinmayr, R.; Wirthwein, L.; Zietlow, A.-L.; et al. (Child and adolescent psychiatry and mental health, 2024)
Children of parents with a mental illness (COPMI) have multiple psychological and developmental risks, including an increased lifetime risk of developing a mental illness themselves. Emotion regulation (ER) has been identified as a potential underlying mechanism of the transgenerational transmission of mental disorders. This study compares ER strategies in parents with and without a mental illness and their children. Further, it aims to examine the relationship between parents and children’s psychopathology with a focus on the role of parental and child ER.
Gesehen am 14.07.2025